Gastroprotective Effect of Aqueous Extract of Unripe Musa Paradisiaca (Banana) Fruit in Rats with Experimentally Induced Gastric Lesions - Zabir, Sharif Mohammad; Hasan, Md Jiaul; Quadir, Rukhsana; Haque, Sumona; Sabiha, Kazi; Ahasan, Md Faizul; Nila, Sabrina Huda; Chowdhury, Abu Saleh Md. Salauddin (Eastern Medical College Journal, 2024)
Background: Unripe banana fruit extract is used to relieve stomach distress in some countries. A few studies in India, China, Sudan, Nigeria and South Africa revealed protection of gastric mucosa after exposed to aggressive agent following administration of unripe banana fruit extract in experimental animals. Objective: To determine the protective effect of aqueous extract of unripe Musa paradisiaca (banana) fruit against ethanol induced gastric lesion in rats. Methodology: This was a prospective experimental study carried out in the department of Pharmacology, Dhaka Medical College, Dhaka within the period from January 2015 to June 2015. Aqueous extract of unripe banana fruit was prepared accordingly. Total 24 rats were randomly divided into 4 groups of 6 in each group. Group-A served as a control group and provided with distilled water (5 ml/kg/body weight) orally by gastric tube. Aqueous extract of Musa paradisiaca was administered orally as Group-B: 0.2 mg/kg/body weight/day, Group-C: 0.4 mg/kg/body weight/day and Group-D: 0.8 mg/kg/body weight/day for 7 days. After 7 days, 1 ml absolute ethanol (a known gastric lesion inducing agent) was orally administered to all groups by gastric tube. After 30 minutes of ethanol administration, all rats were sacrificed and dissected. After separating and opening stomachs, observed lesions were examined and measured with some morphological & histological parameters. Obtained data were subjected to analysis by Student’s unpaired t-test. p-value <0.05 was considered as statistically significant. Results: At the end of experiment, Group-A (control) showed a total of 33 gastric lesions. Group-B, Group-C and Group-D showed 22, 20 and 19 stomach lesions respectively. The difference between control group and experiment groups was statistically significant (p<0.01). Conclusion: The unripe banana fruit extract has dose-dependent gastroprotective effect on rats. So, it may be effective in treating peptic ulcer disease. Eastern Med Coll J. July 2023; 8 (2): 19-23